A COMPARATIVE STUDY ON AGNIKARMA AND INDIGENOUS DRUGS IN THE MANAGEMENT OF JANU SANDHIGATA VATA W.S.R. TO OSTEOARTHRITIS OF KNEE JOINT - Puri, Shubham; Savadi, *B. S. (International Journal of Ayurveda and Pharma Research, 2019)
Sandhigatavata is the most common joint disorder worldwide. Sandhigatavata is a Vatavyadhi affecting people in the Vardhakyaavastha. The disease is characterized by Dhatukshaya and Lakshanas reflective of vitiated Vata. Therefore, the agents / therapies which are Vatahara, Shoolahara and Stambhahara properties should be advised in this disease. The study is focused on rectification of vitiated Vayu by Agnikarma and internal medication which helps to subside the Rooksha and Sheetaguna of Vata. Objectives: The study is aimed to evaluate the efficacy of Indigenous drugs (Indravaruni, Pippaali with Jaggery) in the management of Janusandhigatavata and to compare the effects of Agnikarma and Indigenous drugs in management of Janusandhigatavata. Method: The present study is ‘Comparative clinical trial’. Study was done in two groups. In this study, Agnikarma received group of patients were compared with orally treated group of patients. Result: Comparatively both the groups have almost same significance in the parameters. In terms of two parameters especially in pain and range of movements, Agnikarma treated patients showed very good result. Interpretation: On the basis of the results of both the groups it was observed that, both the groups have almost same significance in the parameters. But Group-B shows more net mean effect and long lasting effect even in follow-up period. With respect to the parameters in pain and in range of movements, Agnikarma treated patients showed very good response. Conclusion: Agnikarma was found very effective in the management of Janusandhigatavata.